MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KERJASAMA DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA - Ulfah Sifti Rahmawati; Luisa Diana Handoyo; Ridwan Rahadiyanto (Lembaga Pendidikan dan Pelatihan Sindotech, 2023)
This class action research aims to determine whether the application of the Problem Based Learning (PBL) learning model can improve the cooperation and learning outcomes of second grade students of SD Kanisius Kembaran. The indicators of the success of this study are the average percentage of student cooperation reaching 75% and the number of students who complete at least 75% with a KKM of 70. The results concluded that the learning steps with the Problem Based Learning (PBL) learning model that can improve student cooperation and student learning achievement consist of five stages, namely orienting students to the problem, organizing students, guiding individual and group investigations, developing and presenting work, and analyzing and evaluating the problem solving process. Based on the observation results, the average percentage of student cooperation in the pre-cycle was 29.09%, in the first cycle action the average student cooperation was 54.55%, and in the second cycle action the average student cooperation was 80%. Meanwhile, from the test results, the average score in the pre-cycle was 58.18. In cycle I action, it increased by 12.50% from pre-cycle activities. Then in cycle II action, the percentage of students who completed was 90.91% with an average score of 89.09. The average score in cycle II action increased by 36.11% from cycle I action. Based on the results of observations during the learning process and the results of the cycle test, it can be concluded that the application of the Problem Based Learning (PBL) learning model can improve the cooperation and learning achievement of grade II students of SD Kanisius Kembaran in the 2022/2023 school year.